(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This descriptive-correlational study assesses the extent of administrators’ leadership skills and employees’ innovation behavior among employees of line agencies in Sulu during the Fiscal Year 2023. With 200 respondents, it employed frequency counts and percentage, weighted mean and standard deviation, t-test for independent samples and One-way ANOVA, and Pearson’s r. This study reveals the following findings: 1) Out of 200 respondents, majority are female, within 30 years old & below and 31-40 years old of age brackets, have permanent status of appointment, have 10 years & below of length of service, and have only bachelor’s degree. 2) Generally, respondents affirmed that administrators of line agencies in possess the needed leadership skills to manage and lead their respective offices. 3) Generally, respondents believed that employees of line agencies in Sulu have positive behavior toward innovation of their services. 4) Variables such as gender, age, length of service, and educational attainment has significant intervene in ways how respondents assess the extent of administrators’ leadership skills. 5) Variables such as gender, age, status of appointment, length of service, and educational attainment has no intervention on how respondents perceive the extent of employees’ innovation behavior. 6) There is a moderate positive correlation between the extent of administrators’ leadership skills and employees’ innovation behavior among line agencies in Sulu.7) This study tends to support Aibiyie (2019) Model of Leadership Skills and Zhao et al. (2022) Model of Employee Innovation Behavior. Accordingly, an organization to its desired goals and objectives, leaders need to possess the following essential skills: strategic planning skills, motivating skills, developing people skills, team building skills, and communication skills. Having these skills, leaders can lead the organization into operation in various types of situations and settings. Similarly, employee innovative behavior which involves processing of new ideas and methods based on existing conditions is instrumental in achieving the goals and objectives by the organization.